(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Environmental pollution is one of the biggest problems of this age, and one of the most dangerous for the future of life on Earth. Most of the scientists differed in determining a precise definition of the scientific concept of environmental pollution, and whatever the scientific concept of radioactive pollution is related primarily to the ecosystem (Eco System), The qualitative and quantitative variation that occurs in the composition of the materials and elements of this system leads to an imbalance in the balance of this system, which leads to direct or indirect effects on the ecosystem, and one of the types of environmental pollution is radioactive pollution, which represents an important and complex problem. Radioactive pollution places an increasing burden on the various components of our environment, including soil, which is a living layer. Many natural, chemical and biological factors interact in their various formation, development and properties. The importance of soil lies in the fact that it is the future of radioactive materials and its long-term role as a repository of radioactive materials and at the same time a source of these materials in air, water and plant pollution. Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample Abstract sample.